Introduction - Perez, R. M.; Carvalho, C. (Etnográfica, 2002)
Edward Said’s seminal text on Orientalism has opened, as it has often been stated, a complex agenda in the social sciences. In fact, Said unambiguously challenged all forms of essentialism by claiming that such settled categories as “Orient” and “Occident” did not correspond to any stable reality, but rather were an odd combination of the empirical and the imaginative (Said 1995: 331). Independent of the enormous controversy – both at the ideological and the theoretical level – that his thesis has raised, his assumption that each age and society recreates its “others” had a strong influence shaping the development of a conceptual apparatus in the colonial discourses of the social sciences and its critiques of colonial rule. The same can be suggested about postcolonial theory.